Nomogram Predicting Bladder Cancer-specific Mortality After Neoadjuvant Chemotherapy and Radical Cystectomy for Muscle-invasive Bladder Cancer: Results of an International Consortium - Mir, Maria Carmen; Marchioni, Michele; Zargar, Homi; Zargar-Shoshtari, K; Fairey, A S; Mertens, Laura S; Dinney, C P; Krabbe, L M; Cookson, M S; Jacobsen, N E; Griffin, J; Montgomery, J S; et al. (European urology focus, 2021)
BACKGROUND: Cisplatin-based neoadjuvant chemotherapy (NAC) for muscle-invasive bladder cancer (MIBC) is associated with improved overall and cancer-specific survival. The post-NAC pathological stage has previously been reported to be a major determinant of outcome. OBJECTIVE: To develop a postoperative nomogram for survival based on pathological and clinical parameters from an international consortium. DESIGN, SETTING, AND PARTICIPANTS: Between 2000 and 2015, 1866 patients with MIBC were treated at 19 institutions in the USA, Canada, and Europe. Analysis was limited to 640 patients with adequate follow-up who had received three or more cycles of NAC. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: A nomogram for bladder cancer-specific mortality (BCSM) was developed by multivariable Cox regression analysis. Decision curve analysis was used to assess the model's clinical utility. RESULTS AND LIMITATIONS: A total of 640 patients were identified. Downstaging to non-MIBC (ypT1, ypTa, and ypTis) occurred in 271 patients (42 %), and 113 (17 %) achieved a complete response (ypT0N0). The 5-yr BCSM was 47.2 % (95 % confidence interval [CI]: 41.2-52.6 %). On multivariable analysis, covariates with a statistically significant association with BCSM were lymph node metastasis (hazard ratio [HR] 1.90 [95% CI: 1.4-2.6]; p < 0.001), positive surgical margins (HR 2.01 [95 % CI: 1.3-2.9]; p < 0.001), and pathological stage (with ypT0/Tis/Ta/T1 as reference: ypT2 [HR 2.77 {95 % CI: 1.7-4.6}; p < 0.001] and ypT3-4 [HR 5.9 {95 % CI: 3.8-9.3}; p < 0.001]). The area under the curve of the model predicting 5-yr BCSM after cross validation with 300 bootstraps was 75.4 % (95 % CI: 68.1-82.6 %). Decision curve analyses showed a modest net benefit for the use of the BCSM nomogram in the current cohort compared with the use of American Joint Committee on Cancer staging alone. Limitations include the retrospective study design and the lack of central pathology. CONCLUSIONS: We have developed and internally validated a nomogram predicting BCSM after NAC and radical cystectomy for MIBC. The nomogram will be useful for patient counseling and in the identification of patients at high risk for BCSM suitable for enrollment in clinical trials of adjuvant therapy. PATIENT SUMMARY: In this report, we looked at the outcomes of patients with muscle-invasive bladder cancer in a large multi-institutional population. We found that we can accurately predict death after radical surgical treatment in patients treated with chemotherapy before surgery. We conclude that the pathological report provides key factors for determining survival probability.
Keywords: Muscles; Prognosis; Cystectomy; Neoadjuvant Therapy; nomogramy; Retrospective Studies; lidé; Urinary Bladder Neoplasms; Humans; retrospektivní studie; svaly; Radical cystectomy; cystektomie; Nomogram; neoadjuvantní terapie; Nomograms; Prediction; nádory močového měchýře; Bladder cancer; Evaluation; Risk